Wodak, R. & Meyer, M. (orgs.). Methods of critical discourse analysis. Londres, Thousand Oaks, Nova Delhi: Sage Publications, 2001, 200 págs. - Ottoni, Maria Aparecida (Cadernos de Linguagem e Sociedade, 2010)
Wodak, R. & Meyer, M. (orgs.). Methods of critical discourse analysis. Londres, Thousand Oaks, Nova Delhi: Sage Publications, 2001, 200 págs.